Fiber bragg grating sensors embedded in polymeric foils - Silva, A. F. (2008)
This paper presents the fabrication and characterization of a polymeric foil able to sense deformation, gather sensitive information and send it for further analysis. Fiber Bragg Grating sensors are embedded in laminated polymeric sheets commonly used in the car’s flooring. The fabrication of the Bragg sensors and the integration of the optic sensors in the foil is described, using industrial fabrication processes. The obtained foil is capable of transferring the full deformation to the optic sensor and returning to the initial position when no deformation exists, providing good sensibility. Application of this sensing foil includes automobile chassis monitoring.